Use of drugs to treat symptoms and acute conditions during pregnancy in outpatient care in Switzerland between 2014 and 2018: analysis of Swiss healthcare claims data (Swiss Medical Weekly, 2021)
BACKGROUND: Evidence on the use of drugs during pregnancy in Switzerland is lacking.OBJECTIVES: To evaluate utilisation of prescribed drugs during pregnancy in outpatient care in Switzerland, focusing on treatments for pain, infections, gastro-oesophageal reflux, nausea/vomiting, and constipation.METHODS: We conducted a descriptive study using the Swiss Helsana claims database (2014–2018). We established a cohort of pregnancies by identifying deliveries and estimating the date of the last menstrual period. We identified claims for the following drugs during pregnancy; analgesics (opioids, paracetamol, and nonsteroidal anti-inflammatory drugs [NSAIDs]), oral antibiotics, antacids, proton pump inhibitors (PPIs), anti-nausea drugs (propulsives and 5HT3-antagonists), and laxatives. Within these drug groups we quantified exposure prevalence to the most prescribed drugs (to >1% of pregnancies) during pregnancy as well as to specific potentially teratogenic or fetotoxic drugs during specific risk periods. Results were extrapolated relative to the demographic distribution of the Swiss population.RESULTS: We identified an extrapolated population of 369,371 pregnancies, with a weighted mean maternal age of 32.0 years (weighted standard deviation 5.1). Analgesics were claimed in 34.5% (95% confidence interval [CI] 33.9–35.0%) of pregnancies, most frequently paracetamol (30.3%, 29.8–30.8%), followed by NSAIDs (8.6%, 8.3–8.8%), and opioids (2.6%, 2.4–2.8%). NSAIDs were claimed in 1.3% (1.2–1.4%) of pregnancies after week 24, and opioids were claimed in 1.3% (1.2–1.4%) in trimester 3. Antibiotics were dispensed in 26.3% (25.8–26.8%) of pregnancies, most frequently amoxicillin (14.6%, 95% CI 14.2–14.9%). Claims for potentially teratogenic or fetotoxic antibiotics during risk periods were each recorded in